Esthetic Root Coverage Of An Isolated Gingival Recession By Lateral Pedicle Graft Technique: A Case Report: Esthetic Root Coverage Of An Isolated Gingival Recession By Lateral Pedicle Graft Technique - Dr. Pathik S. Dholakia; Dr. Jill J. Shah; Dr. Pooja Thumar; Dr. Alankrita Singh Chouhan; Dr. Anuj V. Mansata; Heer T. Bakshi (National Journal of Integrated Research in Medicine, 2022)
Background: Gingival recession is the one of the widespread mucogingival deformity and should be treated at its most primitive recognition. Exposed root surfaces are more likely to develop root sensitivity, root caries, cervical abrasions and post esthetic problems. Amid innumerable procedures, laterally positioned pedicle graft (LPG) is extensively used efficaciously to conceal recession defects. The main advantages of the laterally positioned pedicle graft is, it produces excellent esthetic results as it has good vascularity of the flap and ability to cover the denuded surfaces. Thus, the present case report describes the use of lateral pedicle graft technique in an isolated gingival recession on mandibular incisor. [Dholakia P Natl J Integr Res Med, 2022; 13(1): 123-126, Published on 26/01/2022]